IDENTITAS AYUB YANG DIPERTARUHKAN: SEBUAH PEMBACAAN EKSPOSISIONAL ATAS AYUB 1:1 - Sukmana, Cornelius Iman (PERDIKKATI (Perkumpulan Pendidikan Keagamaan Katolik Indonesia), 2025)
The purpose of this study is to interpret Job's identity in Job 1:1. At the beginning of the Book of Job, a description of Job is written, who is pious, honest, fear of God, and shuns evil. The image is interesting when it is repeated in several texts. The repetition of Job's description of envy relates to his doubts. In this study, Job's identity is interpreted in relation to the stakes placed on Job. As the first sentence of the Book of Job, this verse becomes an exposition that helps understand Job further. Finally, this study concluded that fear of God was the most important thing in Job. Fear of God is fundamental for people who believe in God. Fear of God is the core of the wisdom of the Book of Job.